(untitled) (The Batuk, 2019)
<p">Poets use different forms of representation for nature in their poetry. Poets get relevant subject matters to produce their verse when they encounter different forms of nature in course of their daily lives. Changing seasons and different conditions of nature significantly encourage the poets to express their deeply rooted feelings in multiple ways of representation depicting multiple forms of their surroundings. This article attempts to explore how Laxmiprasad Devkota, the great poet of Nepal, represents the rain in particular and other elements of nature in general in his poem entitled “The Rain.” To deal with the representation of nature in this poem, I have used the tool of ecocriticism that facilitates to study the relationship between literature and nature as well as nature and human beings.